The First Complete Chloroplast Genome Sequence of Mortiño (Vaccinium floribundum) and Comparative Analyses with Other Vaccinium Species - Karla E. Rojas López; Carolina E. Armijos; Manuela Parra; María de Lourdes Torres (Horticulturae, 2023)
Vaccinium floribundum, commonly known as mortiño, is a native high Andean wild species of cultural and economic importance. Genomic resources for V. floribundum are scarce, and a clear phylogenetic and evolutionary history for this species has yet to be elucidated. This study aimed to assemble the complete chloroplast genome sequence of this species and perform an in-depth comparative analysis with other Vaccinium species. The chloroplast genome of V. floribundum was obtained using Oxford Nanopore Technology (ONT). The de novo assembly of the chloroplast genome of V. floribundum resulted in a 187,966 bp sequence, which contained 134 genes (84 Protein Coding Genes (PCGs), 42 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes). The comparative analysis of the V. floribundum chloroplast genome with other nine chloroplast genomes of the Vaccinium species suggested that a contraction/expansion event of the inverted repeat (IR) regions could have occurred, causing the relocation of psbA and rpl32 genes. Additionally, a possible loss of function of the ndhF gene was found. For the phylogenetic analysis based on 87 genes, the chloroplast genome of 19 species (including V. floribundum) was used and revealed that V. myrtillus could be a sister group of V. floribundum. Altogether, our findings provide insights into the plastome characteristics and the phylogeny of V. floribundum. This study describes the complete chloroplast genome sequence of V. floribundum as the first genomic resource available for an Andean species native to Ecuador.